Petrogenesis of late cretaceous arc volcanism in the Eastern Pontides, NE Turkey: insight from zircon U-Pb geochronology, whole-rock geochemistry and Hf-Sr-Nd isotopes - Sar, Abdullah; Kurum, Sevcan; Rizeli, Mustafa Eren; Lee, Hao-Yang (Taylor & Francis Inc, 2024)
The Eastern Pontide Orogenic Belt (EPOB), a well-preserved palaeo-magmatic arc, exists south of the Black Sea, from Bulgaria to Georgia. The region, which forms an essential part of the Alpine-Himalayan belt, contains volcanic rocks formed in the Late Cretaceous. This paper aims to investigate the petrogenesis of the Late Cretaceous volcanic rocks using both new and previously existing geochemical and geochronological data. Based on the geochemical features, the studied volcanics are divided into Group I (dacite/rhyolite) and Group II (basalt/basaltic andesite). According to LA-ICP-MS zircon U-Pb data, the crystallization age of Group I is 83.43 +/- 0.87 Ma. The epsilon Nd(t) values of Group I are -1.4 and + 4.5, and the epsilon Nd(t) value of Group II is +3.0. The Lu-Hf isotope data from zircon shows that Group I have positive epsilon Hf(t) values (+14.20 - +12.15), and their crustal model age is 240-339 Ma. The epsilon Hf(t) values indicate that the Group I rocks are derived from the melting of a depleted mantle source. Whole-rock geochemistry data show that Group II samples were formed by partial melting of metasomatised spinel-bearing lherzolites at shallow depths. It is thought that the Late Cretaceous volcanic rocks are the products of arc magmatism associated with the northward subduction of the Neotethys oceanic lithosphere under the Eurasian plate, and the EPOB was an active continental margin arc during the Late Cretaceous.
Keywords: Geochemistry; U-Pb geochronology; zircon Hf isotope; late cretaceous volcanism; Findikli/rize area; NE Turkey